UWB THz plasmonic microstrip antenna based on graphene - Hussein A. Abdulnabi; Mushreq Abdulhussain Shuriji; Sadiq Ahmed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper proposes design and investigate of graphene based plasmonic microstrip antenna for terahertz high speed communication and application systems (0.1-20) THz. The proposed antenna structure composed of graphene-based rectangular patch and transmission line mounted on a grounded silicone dioxide substrate. SPP (Surface Plasmon Polariton) waves that appear in graphene at THz band is analyzed. The proposed antenna simulation was done by using numerical method CST program. The simulation results show the scattering parameter S11 less than -10 dB at frequency band (0.1-20) THz. Also, the presented antenna system has a good gain along the frequency band.